Exploring the mechanism of YangXue QingNao Wan based on network pharmacology in the treatment of Alzheimer’s disease - Zhang, Yuying; Guo, Kaimin; Zhang, Pengfei; Zhang, Mengying; Li, Xiaoqiang; Zhou, Shuiping; Sun, He; Wang, Wenjia; Wang, Hui; Hu, Yunhui (Frontiers in Genetics, 2022)
It is clinical reported that YangXue QingNao Wan (YXQNW) combined with donepezil can significantly improve the cognitive function of AD patients. However, the mechanism is not clear. A network pharmacology approach was employed to predict the protein targets, and affected pathway of YXQNW in treatment of AD. Based on the random walk evaluation, the correlation between YXQNW and AD was calculated, while a variety of AD clinical approved western drugs were compared. The targets of YXQNW were enriched and analyzed by TSEA platform and MetaCore. We proved that the overall correlation between YXQNW and AD is equivalent to clinical western drugs, but the mechanism of action is very different. Firstly, YXQNW may promote cerebral blood flow velocity by regulating platelet aggregation and vasoconstriction/relaxation signal pathway, which has been verified by clinical Meta-analysis. Secondly, YXQNW may promote Aβ degradation in liver by modulating the abnormal glucose and lipid metabolism via adiponectin dependent pathway, RXR/PPAR dependent lipid metabolism signal pathway and fatty acid synthase activity signal pathway. We also verified YXQNW indeed promote Aβ degradation in hepatic stellate cells. This work provided a novel scientific basis for the mechanism of YXQNW in the treatment of AD.